Thursday
March 23, 2017

Post a New Question

Posted by on Friday, January 20, 2012 at 5:26pm.

find the LCM of y^2+6y+9 and y^2+y-6

  • Algebra - , Friday, January 20, 2012 at 5:32pm

    y^3+6y^2+9y=Y*(Y^2+6Y+9)=Y*(Y+3)^2
    y^2-6y=Y*(Y-6)
    The unique factors are therefore Y, (Y+3)^2 & (Y-6)
    Y*(Y+3)^2*(Y-6) is the lcm

  • Algebra - , Friday, January 20, 2012 at 6:22pm

    y^2 + 6y + 9
    = (y+3)^2

    y^2 + y - 6
    = (y+3)(y-2)

    so LCM = (y-2)(y+3)^2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question